VD_FINDINFO 23/2016/DCA vom 20. Juni 2016 - VD Tribunal cantonal (2016)
RESPONSABILITÉ DES ORGANES D'UNE SOCIÉTÉ, CONSEIL D'ADMINISTRATION, PRESCRIPTION | 680 CO, 716 CO, 716a CO, 717 CO, 718a CO, 754 CO, 756 CO, 760 CO